Pengaruh Ukuran Perusahaan, Debt To Equity Ratio, Dan Net Profit Margin Terhadap Perataan Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Diantari, Pande Putu Maesiya; Wahyuni, Made Arie (Jurnal Akuntansi Profesi, 2025)
This research aims to analyze and test empirically the practice of income smoothing and whether company size, debt to equity ratio and net profit margin have an influence on Income Smoothing in Manufacturing companies on the Indonesia Stock Exchange in the period 2020-2022. This research uses quantitative methods with descriptive statistical techniques as the data analysis technique. Sampling in this study used a purposive sampling technique which was carried out on manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022 so that there were 74 sample companies. The results of this research prove that company size and debt to equity ratio have a negative effect on income smoothing, while net profit margin has a positive effect on income smoothing.